Using probiotics to improve the utilization of chopped dried date palm leaves as a feed in diets of growing Farafra lambs - Hamdon, Hatem A.; Kassab, Ayman Y.; Vargas-Bello-Pérez, Einar; Abdel Hafez, Galal A.; Sayed, Talaat A.; Farghaly, Mohsen M.; Kholif, Ahmed E. (Frontiers in Veterinary Science, 2022)
The study determined the ability of three microbial additives to improve the nutritive value of date palm leaves in diets of growing lambs. Twenty male Farafra lambs (26 ± 0.33 kg) were randomly allocated into four treatments and fed: a control or basal diet (C; 70% concentrate + 30% date palm leaves without additives) and supplemented with Bacillofort containing 2 × 1011 CFU of Bacillus subtilis/g (BAC treatment), Lacotpro containing 1 × 1012 CFU of Lactobacillus acidophilus/g (LAC treatment) or ZAD containing 6 × 108 CFU of R. albus/g (ZAD treatment) at 4 g of all additives for 150 days. LAC improved (P<0.05) growth performance and feed efficiency compared to control. Additives increased (P=0.001) concentrations of albumin, T3 and T4, hemoglobin concentration and RBC and decreased (P=0.001) globulin and urea-N. Additives increased hot carcass (P=0.040) while BAC increased Longissimus dorsi, meat and fat without affecting WHC compared to other treatments. In the metabolism experiment, BAC increased the digestibility of crude protein, while BAC and ZAD increased the digestibility of DM, organic matter and neutral detergent fiber. Additives did not affect N intake and urinary N; however, decreased fecal N and increased N balance compared to the control. BAC and ZAD increased ruminal volatile fatty acids concentration compared to the control. Based on our results, Lacotpro could be used to improve growth performance and feed efficiency, while Bacillofort could be used to improve meat quality of in lambs.